Implementasi Kebijakan Ruang Terbuka Hijau Di Kota Dumai - darlis, erni; As’ari, Hasim; Sujianto, Sujianto (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Dumai City is one of the newly expanded cities in Riau Province, where this area was originally an administrative city with three sub-districts, and is under the main district, namely Bengkalis Regency. In the past, the geographical condition of the Dumai region was a coastal fishing settlement area that developed along its coastline. The purpose of this research is to analyze the implementation, identify the inhibiting factors in implementing the policy, and identify the efforts made by the Dumai City Government in implementing the policy for Green Open Space (RTH) in Dumai City. The form of research that the author uses in writing this research is to use a descriptive method with a qualitative data analysis approach. The result of this research is that the implementation of Green Open Space Policy in Dumai City based on the Regulation of the Minister of Public Works Number 05 of 2008 concerning Guidelines for Provision and Utilization of Green Open Space in Urban Areas is not optimal